A Novel, Comprehensive A129 Mouse Model for Investigating Dengue Vaccines and Evaluating Pathogenesis - Mya Myat Ngwe Tun; Khine Mya Nwe; Jean Claude Balingit; Yuki Takamatsu; Shingo Inoue; Basu Dev Pandey; Takeshi Urano; Michinori Kohara; Kyoko Tsukiyama-Kohara; Kouichi Morita (Vaccines, 2023)
In search of a mouse model for use in evaluating dengue vaccines, we assessed A129 mice that lacked IFN-α/β receptors, rendering them susceptible to dengue virus (DENV) infection. To our knowledge, no reports have evaluated dengue vaccine efficiency using A129 mice. A129 mice were given a single intraperitoneal (IP) or subcutaneous (SC) injection of the vaccine, Dengvaxia. After 14 days of immunization via the IP or SC injection of Dengvaxia, the A129 mice exhibited notably elevated levels of anti-DENV immunoglobulin G and neutralizing antibodies (NAb) targeting all four DENV serotypes, with DENV-4 displaying the highest NAb levels. After challenge with DENV-2, Dengvaxia and mock-immunized mice survived, while only the mock group exhibited signs of morbidity. Viral genome levels in the serum and tissues (excluding the brain) were considerably lower in the immunized mice compared to those in the mock group. The SC administration of Dengvaxia resulted in lower viremia levels than IP administration did. Therefore, given that A129 mice manifest dengue-related morbidity, including viremia in the serum and other tissues, these mice represent a valuable model for investigating novel dengue vaccines and antiviral drugs and for exploring dengue pathogenesis.